2020
DOI: 10.1016/j.cub.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis: The Importance of RHOJ-Mediated Trafficking of Active Integrins

Abstract: In endothelial cells, endo-exocytic traffic of active α5β1 integrins and polarized fibronectin secretion allow vascular morphogenesis. A new study unveils how the endothelial small GTPase RHOJ, by repressing active α5β1 integrin traffic, controls fibronectin polymerization and in vivo angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Rho GTPase signaling networks are critical to the vascular structure and tumor angiogenesis [37]. The small Rho GTPase RhoJ is abundantly expressed in endothelial cells during tumor progression, and its role in angiogenesis has been extensively reported [38][39][40]. Recent studies have revealed that RhoJ blockade destroys tumor blood vessels by activating the RhoA-ROCK signaling pathway in various tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…Rho GTPase signaling networks are critical to the vascular structure and tumor angiogenesis [37]. The small Rho GTPase RhoJ is abundantly expressed in endothelial cells during tumor progression, and its role in angiogenesis has been extensively reported [38][39][40]. Recent studies have revealed that RhoJ blockade destroys tumor blood vessels by activating the RhoA-ROCK signaling pathway in various tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown RHO GTPases signaling contributes to the malignant progression of cancer and some RHO GTPases emerge as a potential therapeutic target [20][21][22][23] , and a new study has uncovered that RHOJ acts as a key regulator of EMT-associated resistance to chemotherapy [24] . In addition, RHOJ interruption has been reported as an effective therapeutic option for targeting the tumor vascular system [25][26][27] . Our recent studies also showed that RHOJ is significantly overexpressed in glioblastoma and facilitates angiogenesis and tumor invasion [28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…FMNL2 regulates β1 integrin internalization [ 29 ] but is reported to be absent in endothelial cells [ 30 ]. Therefore, the closely related protein FMNL3, already known to function downstream of RhoJ during lumenisation [ 19 ] and downstream of Cdc42 at the Golgi during anterograde trafficking [ 31 ] is a likely shared effector that could regulate RhoJ-dependent regulation of active α5β1 trafficking [ 32 ].…”
mentioning
confidence: 99%